The non-indigenous and invasive species Paraleucilla magna Klautau, Monteiro & Borojevic, 2004 (Porifera: Calcarea) in the Algerian coast (Southwestern of Mediterranean Sea) - Bachetarzi, Rym (Array, 2019)
The non-indigenous and invasive calcareous sponge Paraleucilla magna Klautau, Monteiro & Borojevic, 2004 has been detected for the first time on the Algerian coast. The species has been recorded at high abundance in Algiers Port (Algiers) and in Pisan Island (Béjaïa) during spring 2018. It was present from 2 m to 20 m of depth at the community of seaweeds with filter feeders established on artificial hard substrates and on rocky boulders. Total of 172 individuals were recorded not exceeding 5 cm in height. Anthropogenic activities such as aquaculture farms or shipping traffic might be important vectors or act as stepping-stones in further expansion of Paraleucilla magna.Additional recording of the species adds to the knowledge of its biogeography distribution, biology and ecology in the Mediterranean and may improve selection of key geographical sites for future monitoring on the species proliferation and expansion.